Percepcije organizacijske kulture turistične destinacije - Šuligoj, Metod (Teorija in praksa, 2016)
The paper is focused on the organisational culture of the tourism industry in the tourist destination of Portorož. The purpose of the research was to determine differences between managers and employees and, separately, between the two genders in view of the factors of organisational culture. First, based on a compilation and comparison we developed a theoretical basis for the empirical research. In addition, using a questionnaire we collected 149 views of respondents employed in four sectors of the tourism industry. Due to the non-normal distribution of the sample, the nonparametric Mann-Whitney test was used to detect differences and, in addition, to determine any differences between genders an independent samples t-test was employed. Finally, no statistically significant differences were found between managers and employees in the vast majority of variables; this also applies to gender differences.
Keywords: Organizacijska kultura; Organizational culture; Portorož (Slovenia); Portorož (Slovenija); raziskave; Tourism; Turizem